Fundamentals Of Entrepreneurship (ENT300) : Glitter Exclusive / Siti Nur Hafiza Mohd Akhir - Mohd Akhir, Siti Nur Hafiza (2020)
GLITTER EXCLUSIVE is my sole proprietorship business. The development of this business began when I had a good commitment and dedication to build a business. Opportunities for the success of Glitter Exclusive exist as the sophistication of technology expands every year. Glitter Exclusive is poised to capitalize on this growth and modest competition in the industry with dedicated and experienced staff, excellent networking, and effective management and marketing. The main business of Glitter Exclusive is a business that provides painting and renewing roads to places that have low-lit roads. These painting services are different from others because my business provides glow in the dark paint that allows road users to see better in dark roads that do not provide lights especially in rural areas in Malaysia. Gelugor, Penang has been chosen by my company because it is strategically located in central Malaysia and this area is currently located near my business’s paint supplier as well as my workers. This idea of a smart highway was derived from an idea already done by Designer Daan Roosegaarde and Haejmans Infrastructure. This smart highway is an interactive and sustainable road of tomorrow that may able to reduce the usage of electricity in Malaysia. My objective is to provide a service that is able to ensure the safety of road users living in rural areas that live with minimal or no conventional lighting as my glitter in the dark lines may help them to see better at night. Besides that, glitter is a business that wishes to be the first glitter on the dark road in Malaysia as well as Asia because of the conditions of the roads in Malaysia. I believe that I am able to make a difference in changing and improving the roads I already have.